What Caused Recent Shifts in Tropical Pacific Decadal Sea‐Level Trends?. Issue 11 (11th November 2019) - Piecuch, Christopher G.; Thompson, Philip R.; Ponte, Rui M.; Merrifield, Mark A.; Hamlington, Benjamin D.
Abstract: Satellite altimetry reveals substantial decadal variability in sea level ζ across the tropical Pacific during 1993–2015. An ocean state estimate that faithfully reproduces the observations is used to elucidate the origin of these low‐frequency tropical Pacific ζ variations. Analysis of the hydrostatic equation reveals that recent decadal ζ changes in the tropical Pacific are mainly thermosteric in nature, related to changes in upper‐ocean heat content. A forcing experiment performed with the numerical model suggests that anomalous wind stress was an important driver of the relevant heat storage and thermosteric variation. Closed budget diagnostics further clarify that the wind‐stress‐related thermosteric ζ variation resulted from the joint actions of large‐scale ocean advection and local surface heat flux, such that advection controlled the budget over shorter, intraseasonal to interannual time scales, and local surface heat flux became increasingly influential at longer decadal periods. In particular, local surface heat flux was important in contributing to a recent reversal of decadal ζ trends in the tropical Pacific. Contributions from local surface heat flux partly reflect damping latent heat flux tied to wind‐stress‐driven sea‐surface‐temperature variations. Key Points: Sea level in the western tropical North Pacific and eastern and central equatorial Pacific underwent decadal variation over 1993–2015 This decadal variation reflects ocean heat storage related to ocean heat transport and local surface heat flux due to anomalous wind stress Contributions from air‐sea heat exchange arise from latent heat flux associated with wind‐stress‐related sea‐surface temperature changes